APPLICATION OF ISLAMIC TEACHING VALUES IN EDUCATION: CREATING STUDENTS WITH SIDDIQ, AMANAH, TABLIG, AND FATONAH CHARACTERS - Ghozali, Imam (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and understand the process of internalizing the values of Islamic teachings in forming students with Siddiq, Amanah, Tablig, and Fatonah characters. This research is a qualitative descriptive case study type research. The case study in this research is in-depth research about an individual, a group, an organization, an activity program, and so on at a specific time. This type of descriptive research aims to explore and describe social reality, describing many variables related to the problem and unit being studied. This research was conducted at the institution at MA Miftahul Ulum Pakuniran Probolinggo. The data analysis technique in this research uses the Miles and Huberman data analysis model with stages of data reduction, data display, and conclusion. The results of the research conducted show that the application of internalizing the values of Islamic teachings forms students with Siddiq, Amanah, Tablig, and Fatonah characters, including (1) Transformation of Islamic teaching values in forming students with the four characteristics of the prophet at MA Miftahul Ulum Pakuniran. The transformation stage is carried out by distributing material by PAI teachers. (2) Transaction of Islamic teaching values in forming students with the four characteristics of the prophet at MA Miftahul Ulum Pakuniran. In the transaction stage, the teacher discusses the material with students in the classroom. (3) Transinternalization of Islamic teaching values in forming students with the four characteristics of the prophet at MA Miftahul Ulum Pakuniran. The teacher's transinternalization stage provides examples, familiarizes with, implements, and forms student character student activities in daily life in the school environment.